2010
DOI: 10.1088/0960-1317/20/3/035003
|View full text |Cite
|
Sign up to set email alerts
|

Droplet merging in a straight microchannel using droplet size or viscosity difference

Abstract: In the present study, a novel droplet-merging technique is proposed, which enables two nanoliter or picoliter droplets to merge in a straight microchannel with high precision. Two dispersed phase fluids are supplied respectively from two side channels in a certain range of flow rates to generate droplets of different sizes or different viscosities in a regularly alternating mode at a cross-channel intersection prior to the straight microchannel, in such a manner that the droplets are spontaneously synchronized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…7a, c respectively) suggests that the change in topology from S 1 (λ < 1) to S 3 (λ > 1) is attributable to the increase in λ. Droplet circulation is suppressed and a more uniform flow pattern is established in 5 the more viscous S 3 droplets which can be explained on the basis of Equation (1). The observed changes in the droplet flow pattern are also illustrated analytically by Jin et al 38 for capillary droplet flows. Their analytical velocity profiles showed that at low λ, the droplet tended to adopt a parabola-like topology in the bulk-10 volume, whereas with increasing λ, a more uniform distribution was established.…”
mentioning
confidence: 69%
“…7a, c respectively) suggests that the change in topology from S 1 (λ < 1) to S 3 (λ > 1) is attributable to the increase in λ. Droplet circulation is suppressed and a more uniform flow pattern is established in 5 the more viscous S 3 droplets which can be explained on the basis of Equation (1). The observed changes in the droplet flow pattern are also illustrated analytically by Jin et al 38 for capillary droplet flows. Their analytical velocity profiles showed that at low λ, the droplet tended to adopt a parabola-like topology in the bulk-10 volume, whereas with increasing λ, a more uniform distribution was established.…”
mentioning
confidence: 69%
“…Partially confined, high viscosity droplets undergo a stronger viscous dissipation and therefore move slower than low viscosity droplets of equal radius (and confinement). This allows low viscosity droplets to catch up with high viscosity droplets, resulting in coalescence [27]. Similarly, droplets of different radius behave differently.…”
Section: Drag Force and Viscous Dissipationmentioning
confidence: 99%
“…Since the droplet pairs with different compositions are possible to be formed, it can be used for indexing the concentrations of solutes in a droplet, protein crystallization 13 or used as an initial process in droplet-merging techniques. [14][15][16] The stable formation of droplets is expected in such a way that the miniature volume of each dispersed flow is controllable as accurately as possible. As a result, investigations on the dynamic behavior of multiphase flows in a microfluidic double T-junction device are required in order to determine flow conditions, channel geometries, and fluid properties for generating stable alternating droplets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the formation of different droplets by using different viscosities of two dispersed flow streams or different flow rates was shown by Jin et al 14 Empirical formulas of flow rate range of dispersive flow fluids were also proposed in his paper with the aim of choosing the best inflow conditions for alternating droplet formation (ADF). Another form of the double T-junction that includes tapered expansion chamber and two triangular wings placed at T-junction was also used to generated ADF by reducing the flow instability and preventing reagents from back flowing.…”
Section: Introductionmentioning
confidence: 99%